Penguatan Daya Saing UMKM Melalui Edukasi Pemasaran Digital di Sonopakis Lor, Kabupaten Bantul - Niken Permata Sari; Bhenu Artha; Utami Tunjung Sari; Antonius Satria Hadi; Adista Ika Julia (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector in Bantul Regency faces significant challenges regarding the digital divide , with approximately 40 percent of business actors still relying on conventional operational methods that are vulnerable to economic volatility. This community service activity aims to strengthen the competitiveness of 7 MSME actors in Sonopakis Lor through holistic and strategic digital marketing education. The method applied is Participatory Action Research (PAR) , which positions business actors as active subjects through structured knowledge transfer mechanisms and intensive micro-mentoring (hands-on practice). The intervention, conducted on April 23, 2026 , included technical training on Google My Business , social media optimization based on Marketing 4.0 and 5.0 , and content marketing strategies that integrate local wisdom values as intangible assets. Results indicate the successful assimilation of participants in mastering the digital ecosystem , including the ability to recalibrate Cost of Goods Sold (COGS) structures to anticipate platform service fees and e-commerce logistics costs. This program successfully triggered a structural cognitive paradigm shift , where participants now perceive digital transformation as a vital instrument for business resilience and long-term competitive advantage in the post-modern economic era. This synergy underscores the crucial role of academics in demystifying technological complexities into adaptive tactical steps for the grassroots economy